Evaluasi Pengelolaan Program KIP Kuliah di Sekolah Tinggi Ilmu Administrasi Banten: Pendekatan Model CIPP - Rizal Bahtiar Bahtiar; Arif Nugroho (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to evaluate the management of the Indonesia Smart Card for Higher Education (KIP Kuliah) Program at the School of Public Administration (STIA) Banten using the CIPP evaluation model (Context, Input, Process, Product). The KIP Kuliah Program is a government initiative to provide access to higher education for underprivileged yet high-achieving students. This research employs a descriptive qualitative method through observation, interviews, documentation, and interactive data analysis based on the Miles and Huberman model. The results show that, in terms of context, the program aligns with the needs of STIA Banten students. However, in the input aspect, there are still limitations in human resources and the digital system has not been optimized. The implementation process lacks transparency, with administrative selection involving minimal field verification and uneven dissemination of information. Regarding the product, the program has provided financial assistance and academic motivation, but it has not yet produced a sustained improvement in student performance. Therefore, it is necessary to strengthen the capacity of program managers, develop integrated digital information systems, and ensure continuous monitoring to achieve program effectiveness and sustainability.